Respuesta :

msm555

Answer:

Solution given:

a.

p=2/3

q=-1/3

r=1/6

now

p-q+r=2/3-(-1/3)+1/6

=[tex]\frac{2*2+1*2+1}{6}=\frac{7}{6}[/tex]

c.

p=-1/5

q=-3/10

r=2/5

now

p-q+r=-1/5-(-3/10)+2/5

=[tex]\frac{-1*2+3+2*2}{10}=\frac{5}{10}=½[/tex]

Answer:

  • a) 1 1/6
  • c) 1/2

Step-by-step explanation:

The expression given:

  • p - q + r

Evaluate for each case:

a)

p = 2/3, 1 = -1/3, r = 1/6

  • p - q + r =
  • 2/3 - (-1/3) + 1/6 =
  • 2/3 + 1/3 + 1/6  =
  • 1 + 1/6 =
  • 1 1/6

c)

p = 1/-5, q = -3/10, r = 2/5

  • p - q + r =
  • -1/5 - (-3/10) + 2/5 =
  • -2/10 + 3/10 + 4/10 =
  • 5/10 =
  • 1/2